Long‐term efficacy and safety of alemtuzumab in advanced primary cutaneous T‐cell lymphomas. (March 2014) - de, A.; Guitera, P.; Brice, P.; Moulonguet, I.; Mouly, F.; Bouaziz, J.‐D.; Battistella, M.; Madelaine, I.; Roux, J.; Ram‐Wolff, C.; Cayuela, J.‐M.; Bachelez, H.; et al.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Alemtuzumab has shown short‐term efficacy in small numbers of patients with advanced primary cutaneous T‐cell lymphomas. What does this study add? Alemtuzumab may induce long‐term remission (> 2 years) in patients with Sézary syndrome. Alemtuzumab is poorly effective in nontransformed mycosis fungoides and transformed CTCL.